Identification of α-glucosidase inhibitors from Mulberry using UF-UPLC-QTOF-MS/MS and molecular docking. (February 2023) - Abudurexiti, Adalaiti; Zhang, Rui; Zhong, Yewei; Tan, Huiwen; Yan, Junlin; Bake, Subinuer; Ma, Xiaoli
Graphical abstract: Highlight: In this study, mulberry was used as a natural drug candidate for the screening of α-glucosidase inhibitory components of mulberry extracts by affinity ultrafiltration liquid mass spectrometry. Molecular docking studies showed that these small molecules were more likely to occupy the active site of α-glucosidase than the positive control Acarbose, scoring above the threshold, suggesting that mulberry is a potential source of hypoglycaemic agents. Cellular experiments revealed that the extracted parts and some monomeric compounds of Mulberry extract improved insulin resistance to some extent. Abstract: As a medicinal and edible plant, Mulberry has shown good hypoglycaemic activity at the animal level, but its active ingredients and hypoglycaemic mechanisms remain unclear. In this study, we used ultrafiltration-ultra performance liquid chromatography-quadrupole time-of-flight-mass spectrometry (UF-UPLC-QTOF-MS/MS) and molecular docking to screen for high-affinity α-glucosidase inhibitors in Mulberry. Our innovation was to determine the inhibitory activity of Mulberry extracts in vitro and screen the active small molecules in the extracts using advanced UF-UPLC-QTOF-MS/MS techniques and validate these compounds at the molecular docking and cellular levels, laying the foundation for studying the mechanism of type 2 diabetes in Mulberry. α-Glucosidase incubation experiments showed that the IC50 value of Mulberry crude extracts was 37.58 μg/mL. Six possible α-glucosidase activity inhibitory components were identified using UF-UPLC-QTOF-MS/MS. Molecular docking studies showed that these small molecules were more likely to occupy the active site of α-glucosidase than the positive control acarbose, scoring above the threshold, indicating that Mulberry is a potential source of hypoglycemic agents. Further cellular level studies showed that different extracts and active small molecules of Mulberry improved insulin resistance in HepG2 cells. Through the analysis of glucose-lowering targeting components, the subject clarified that Mulberry exerts therapeutic effects on Diabetes Mellitus (DM) through a multi-component, multi-target, and multi-pathway relationship, which is consistent with Traditional Chinese Medicine (TCM) theory as a potential source of glucose-lowering agents.